Ergonomic Mobility Aid Redesign for Older Adults Using QFD and Concurrent Engineering - susmitha canny; Bagus Anugrah Ramadhan; Nur Fitria Ningsih (Telkom University, 2025)
Global increases in life expectancy have led to a growing proportion of older adults experiencing functional decline and mobility limitations. In Indonesia, older adults account for 11.75% of the population, with musculoskeletal disorders being a major cause of disability and fall-related injuries. Mobility aids are essential to support independence and reduce fall risk. However, many existing designs lack adequate ergonomic considerations, limiting comfort and usability. This study aimed to optimize mobility aid design by applying ergonomic principles and a user-centered development approach to improve safety, functionality, and quality of life among older adults. Quality Function Deployment (QFD) was used to translate user needs into technical specifications, while Concurrent Engineering was applied to integrate ergonomic and technical considerations throughout the design and prototyping stages. The resulting design incorporates adjustable height, a foldable seat, lightweight durable materials, and a reliable braking system. Verification confirmed compliance with key technical requirements, including a handbrake force of 120 N and a height adjustment range of 75–88 cm. Validation with 30 older adult users demonstrated high satisfaction, particularly with stability and braking performance. Overall, the proposed mobility aid shows potential to enhance safety, usability, and functional independence among older adults.